Structuralism in modern business-cycle theory: A framework for a structuralist reconceptualization - Peter Galbács (Duke University, Center for the History of Political Economy (CHOPE), 2017)
In this tiny paper, a possible framework for a structuralist analysis of modern business-cycle theory is considered. In order to respond to the debates around the realist and instrumentalist interpretations of the works of Friedman I will provide a framework in which the tension between the opposite standpoints can be overcome. Based on epistemic structural realism, firstly, I will identify Friedman's stance as a mix of agent-level instrumentalism and macro-level causal realism and, secondly, I will scrutinize the consistency of this epistemic strategy. I will argue that causal realism requires one to be realist regarding the assumptions defining agents as well.
Keywords: B22; B41; 330; structural realism; entity realism; business-cycle theory; unrealistic assumptions